The syntaxin homolog AtPEP12p resides on a late post-Golgi compartment in plants. - da Silva Conceição, A (1997)
Soluble proteins are transported to the plant vacuole through the secretory pathway via membrane-bound vesicles. Targeting of vesicles to appropriate organelles requires several membrane-bound and soluble factors that have been characterized in yeast and mammalian systems. For example, the yeast PEP12 protein is a syntaxin homolog that is involved in protein transport to the yeast vacuole. Previously, we isolated an Arabidopsis thaliana homolog of PEP12 by functional complementation of the yeast pep12 mutant. Antibodies raised against the cytoplasmic portion of AtPEP12 have been prepared and used for intracellular localization of this protein. Biochemical analysis indicates that AtPEP12 does not localize to the endoplasmic reticulum, Golgi apparatus, plasma membrane, or tonoplast in Arabidopsis plants; furthermore, based on biochemical and electron microscopy immunogold labeling analyses, AtPEP12 is likely to be localized to a post-Golgi compartment in the vacuolar pathway.